POTRAIT OF ENVIRONMENTAL DAMAGE IN THE NOVEL ISINGA ROMAN PAPUA BY DOROTHEA ROSA HERLIANY: AN ECORITICAL STUDY - Mutaqin, Diki; Muliawati, Hesti (Cirebon International Conference on Education and Economics Proceeding, 2024)
This article discusses the portrait of environmental damage that occurred in the interior forest areas of Papua in the Novel Isinga Roman Papua by Dorothea Rosa Herliany. This research uses a descriptive analysis method using literary ecocriticism theory and a discourse approach. To be able to understand the portrait of environmental damage that occurred in Isinga, this research uses the ecocritical theory put forward by Greg Garrard. The research results indicate that the novel can describe environmental damage in the form of pollution, wilderness, apocalypse, dwelling, animals and earth. Based on the six indicators of environmental damage contained in the novel, it can be concluded that Isinga tries to show the environmental damage that occurs in the novel in the form of its causes and impacts through events involving the characters.